Study And Analysis Of Parental Neglect And Its Role In Increasing The Hostile Behavior Of The Child Towards Family Members And Society - Hussein Hameed, Safaa; Hadi Hussein, Nagham (Opción, 2019)
This study aims to find out the relationship between the child’s aggressive be- havior and verbal abuse on the part of the mother and neglect as it aims to find out the differences between boys and girls at the level of aggressive behavior . The research sample consisted of (65) school children aged (11-13) years. The study tools are: the Aggressive Behavior Scale and the Parental Abuse Scale. The results obtained are: - The presence of statistically significant correlation between verbal abuse and aggressive behavior and between neglect and ag- gressive behavior among school children. - The presence of statistically signifi- cant differences in aggressive behavior among school children in favor of boys.